2022
DOI: 10.1111/inr.12793
|View full text |Cite
|
Sign up to set email alerts
|

Impact of compassion satisfaction and compassion fatigue on satisfaction with life in Serbian and Polish nurses: A cross‐sectional study

Abstract: Aims and objectives:To evaluate demographic and occupational factors of professional life on life satisfaction among nurses in Serbia and Poland. Background: Compassion satisfaction and compassion fatigue, as aspects of a nurse's professional life, may affect their satisfaction with life in general. However, most studies on this topic have been conducted in Asian countries, and because there are differences in health care system performance across countries amid a global shortage of nurses, it is necessary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Furthermore, differences were found between men and women when evaluating other people's emotions, with women showing higher scores. This is corroborated by studies that reported that women show better emotional intelligence skills [18], can better recognize their own and others' emotions, and show greater levels of perception and empathy than men [21].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Furthermore, differences were found between men and women when evaluating other people's emotions, with women showing higher scores. This is corroborated by studies that reported that women show better emotional intelligence skills [18], can better recognize their own and others' emotions, and show greater levels of perception and empathy than men [21].…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, subjects with high emotional intelligence, who can associate others' emotions along with their own, have good satisfaction with life, a consequence of each individual's assessment of their life according to their past and present [17]. Other variables not studied in this research, such as job satisfaction, financial situation, compassion fatigue, and education, should also explain life satisfaction [18].…”
Section: Discussionmentioning
confidence: 89%
“…A recent study of nursing staff demonstrated that nurses who were dissatisfied with their lives were more likely to suffer from psychological disorders, with a risk as high as 2.4 times (Zakeri et al, 2021). Numerous studies have discovered that nurses' life satisfaction is associated with resilience, gratitude disposition, job satisfaction, compassion, and self-efficacy (Yu and Lee, 2018;Zakeri et al, 2021;Milutinović et al, 2022). Furthermore, life satisfaction is positively correlated with occupational burnout, and nurses with low life satisfaction are prone to occupational burnout (Zborowska et al, Qin et al 10.3389/fpsyg.2023.1125465 Frontiers in Psychology 02 frontiersin.org 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers have primarily focused on sociodemographic and occupational risk factors for life satisfaction (Milutinović et al., 2022; Piotrkowska et al., 2019), providing relatively little insight into facilitative or protective factors and underlying psychological mechanisms. Considering the asset‐based paradigms of positive psychology (Clarke et al., 2020), we examined the underlying mechanisms by which interpersonal assets (i.e., social connectedness), the positive side of the work‒family interface (work‒family enrichment) and intrapersonal strength (i.e., self‐concept clarity) predict life satisfaction among Chinese nurses.…”
Section: Introductionmentioning
confidence: 99%